Prevalence of Vitamin D deficiency in children aged 02–12 years attending outpatient service in a hospital in North East India - Parminder Singh Rooprai,; Divya Gupta, (Indian Journal of Child Health, 2021)
Objective: This study was done to assess the Vitamin D status in children between age group of 2 and 12 years attending outpatient department (OPD) services. Materials and Methods: This cross-sectional observational study was done from September 2017 to August 2018 in a hospital in Tezpur, Assam. A total of 281 children were included in the study and serum 25-hydroxy vitamin-D (25(OH)D), calcium, phosphorus, and alkaline phosphatase were measured in the fasting state. Deficiency was defined as 25(OH)D values 30 ng/mL. Results: The prevalence of Vitamin D deficiency was found to be 21.1% and that of Vitamin D insufficiency to be 12.2%. We did not find any significant association between serum 25(OH)D and other factors such as duration of sunlight exposure or other biochemical parameters such as serum calcium, phosphorus, and alkaline phosphate levels. Conclusion: There was a high prevalence of biochemical hypovitaminosis D (deficiency and insufficiency) in children attending OPD in a hospital in northeast India.